2006
DOI: 10.1086/505582
|View full text |Cite
|
Sign up to set email alerts
|

HIV Coinfection Impairs CD28‐Mediated Costimulation of Hepatitis C Virus–Specific CD8 Cells

Abstract: These results indicate that, during HCV/HIV coinfection, memory-effector CD8 cells have reduced responsiveness to CD28 costimulation. This appears to reflect a global effect that HIV has on the activation or differentiation state of CD8 cells that are responsive to other microbial pathogens. This functional defect has implications for the pathogenesis of HCV/HIV coinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…On the other hand, HCV-specific CD8 ϩ T cells have an earlier memory phenotype (i.e., CD28 ϩ CD27 ϩ ), whereas CMV-specific T cells have a late effector phenotype (i.e., CD27 Ϫ 28 Ϫ ) [9]. Our current study confirms previously reported findings that HIV ϩ persons have fewer CD8 ϩ CD28 ϩ T cells than do HIV Ϫ persons, whereas HCV ϩ persons have more CD8 ϩ CD28 ϩ T cells than do HCV Ϫ persons [8,12,13]. Additionally, we found that HIV ϩ HCV ϩ RNA ϩ women have increased CD8 ϩ 28 ϩ HLA-DR ϩ T cells.…”
Section: Immune Activation Is a Hallmark Of Human Immunodeficiency VIsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, HCV-specific CD8 ϩ T cells have an earlier memory phenotype (i.e., CD28 ϩ CD27 ϩ ), whereas CMV-specific T cells have a late effector phenotype (i.e., CD27 Ϫ 28 Ϫ ) [9]. Our current study confirms previously reported findings that HIV ϩ persons have fewer CD8 ϩ CD28 ϩ T cells than do HIV Ϫ persons, whereas HCV ϩ persons have more CD8 ϩ CD28 ϩ T cells than do HCV Ϫ persons [8,12,13]. Additionally, we found that HIV ϩ HCV ϩ RNA ϩ women have increased CD8 ϩ 28 ϩ HLA-DR ϩ T cells.…”
Section: Immune Activation Is a Hallmark Of Human Immunodeficiency VIsupporting
confidence: 90%
“…We previously published the finding that coinfected women have increased primed activated T cells (i.e., CD8 ϩ CD45RO ϩ CD27 ϩ 95 ϩ ), compared with HIV ϩ HCV Ϫ women [6], and postulated that this population of cells represented effector/central memory T cells. The population of activated CD8 ϩ 28 ϩ cells in our current study may also represent early central memory T cells and further suggests that HCV may be playing a role in skewing CD8 ϩ maturation toward an earlier phenotype [6,9,[11][12][13].…”
Section: Immune Activation Is a Hallmark Of Human Immunodeficiency VImentioning
confidence: 57%
“…Notably, we did not distinguish between CD4 and CD8 responses in these assays, so we cannot comment on whether this compartmentalization encompasses CD4, CD8, or both subsets of T cells. Our demonstration of HCV-specific T-cell responses within the IHL and PBL compartments in under half of the subjects is similar to responses previously found in the PBL compartment of chronic HCVinfected patients with compensated liver function, using the same assay method (47). This underscores the paucity of IFN-␥-producing T cells previously described for the PBL compartment (16,24,25,(42)(43)(44) and extends the observation to the IHL compartment in the setting of direct ex vivo assays.…”
Section: Vol 82 2008 Liver and Perihepatic Lymph Node Lymphocytes 1supporting
confidence: 87%
“…Proliferative function was measured by thymidine incorporation. The use of 10 pools of HCV peptides allows for analysis of the HCV-specific immune response to 441 possible 18-mer peptides with a limited number of cells (47). Mitogen-induced IFN-␥ and proliferation responses were measured to ensure cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Liver fibrosis progression may be related to weak cellular immune responses to HCV antigens in HIV infected patients. HIV infection is characterized by marked decreases in the number of circulating CD4 cells, functional impairment of both CD4 and CD8 cells and down-regulation of CD28 expression (a costimulatory molecule required for effective lymphocyte activation) [102]. Patients with lower CD4 cells have less HCV specific CD8 cells responses and this could explain the more advanced liver disease progression since CD8 cells responses are thought to be of primary importance in the immune response to viral infection.…”
Section: Epidemiologymentioning
confidence: 99%